Nonlinear Stress‐Induced Transformations in Collagen Fibrillar Organization, Disorder and Strain Mechanisms in the Bone‐Cartilage Unit - Badar, Waqas; Inamdar, Sheetal R.; Fratzl, Peter; Snow, Tim; Terrill, Nicholas J.; Knight, Martin M.; Gupta, Himadri S. (Advanced science, 2025)
By developing a 3D X‐ray modeling and spatially correlative imaging method for fibrous collagenous tissues, this study provides a comprehensive mapping of nanoscale deformation in the collagen fibril network across the intact bone‐cartilage unit (BCU), whose healthy functioning is critical for joint function and preventing degeneration. Extracting the 3D fibril structure from 2D small‐angle X‐ray scattering before and during physiological compression reveals of dominant deformation modes, including crystallinity transitions, lateral fibril compression, and reorientation, which vary in a coupled, nonlinear, and correlated manner across the cartilage‐bone interface. A distinct intermolecular arrangement of collagen molecules, and enhanced molecular‐level disorder, is found in the cartilage (sliding) surface region. Just below, fibrils accommodate tissue strain by reorientation, which transitions molecular‐level kinking or loss of crystallinity in the deep zone. Crystalline fibrils laterally shrink far more (20×) than they contract, possibly by water loss from between tropocollagen molecules. With the calcified plate acting as an anchor for surrounding tissue, a qualitative switch occurs in fibrillar deformation between the articular cartilage and calcified regions. These findings significantly advance this understanding of the complex, nonlinear ultrastructural dynamics at this critical interface, and opens avenues for developing targeted diagnostic and therapeutic strategies for musculoskeletal disorders. The ultrastructural mechanisms enabling physiological compression in cartilage/bone interfaces in joints are explored using X‐ray nanomechanical imaging and 3D modeling of the hydrated collagen fibril/proteoglycan nanostructure. The approach reveals synergistic and microscale spatially‐graded stress‐induced interactions between hidden modes like fibrillar compaction, fluid flow, crystallinity transitions, and reorientation. These molecular‐to‐microscale biophysical mechanisms advance fundamental understandings of joint function and pathological degeneration.